Disaster Management of Forest and Peatland Fire Through The Berdikari Gambut Village Program in Pakning River, Bengkalis District - Wahyu Purwanto; Rahmad Hidayat; Anugraheni Utami (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
Riau is one of the areas that often occurs due to haze disasters due to forest and land fires in Indonesia. One of the causes of fire is difficult to extinguish because most of the burned area is peatland. Several attempts have been made to deal with this forest and land fire disaster, both from the government, community and private sector. In this paper, we will discuss how to overcoming land and forest fire disasters in the Sungai Pakning, Bengkalis Regency through the PT Pertamina RU II Sungai Pakning Kampung Gambut Berdikari CSR program. The research method used descriptive qualitative research. The result is that the Kampung Gambut Berdikari Program is able to overcome the problem of land and forest fires in the Sungai Pakning, as evidenced in 2018 to 2020 in the Sungai Pakning region there has been no forest and land fires again (zero fire).